Pharmacokinetics of thiamine (vitamin B1) in adult horses after administration of three single intravenous doses. Issue 6 (18th August 2021) - Hess, Emily K.; Reinhart, Jennifer M.; Anderson, Melinda J.; Jannasch, Amber S.; Taylor, Sandra D.
Abstract: Thiamine is a vital co‐factor for several anti‐inflammatory and antioxidant processes that are critical for mitigation of sepsis‐associated inflammation, but pharmacokinetic (PK) analysis has not been reported in horses. We hypothesized that IV thiamine hydrochloride (TH) at increasing dosages would result in corresponding increases in plasma thiamine concentrations without causing adverse effects. A randomized cross‐over study was performed in 9 healthy horses that each received TH at 5, 10, and 20 mg/kg IV. Blood was collected immediately prior to drug administration and at several time points thereafter. High‐performance liquid chromatography with mass spectrometry was used to quantify thiamine concentrations at each time point. Non‐compartmental PK methods showed that IV TH resulted in supraphysiologic plasma concentrations with a short half‐life (0.77–1.12 h) and no adverse clinical signs were observed. The terminal rate constant decreased as the dosage increased ( p  < .0001) and clearance significantly decreased at the 20 mg/kg dosage ( p  = .0011). The area under the curve (AUC) increased in a non‐linear fashion. These findings suggest that thiamine follows non‐linear elimination kinetics in horses, which is likely due to saturation of renal elimination. Future studies are needed to identify therapeutic plasma concentrations and develop thiamine dosing recommendations for horses.